Optimising Cash Conversion Cycle Using Account Receivable Management As Response To The Impact Of The Covid-19 Pandemic (Case Study: Pt ABC) - Husni, Sulhi (Journal of Economics and Business UBS, 2023)
PT ABC is the largest ground handling company in Indonesia. PT ABC is one of the companies in the aviation industry that has been affected by the covid-19 pandemic. PT ABC is currently experiencing problems in the cash conversion cycle which has an impact on the company's working capital. This problem had started before the Covid-19 pandemic and was exacerbated by the pandemic. The average collection period required by PT ABC during the 2017 – 2021 period is 96 days, while similar companies in the same industry only need 61 days. Therefore, this study will focus on optimizing the receivables collection period and analysing the Cash Conversion Cycle by creating a simulation for companies with the method of tightening credit standards and giving cash discounts. Based on the research conducted, the authors found that giving price discounts is the most appropriate way to optimize working capital accompanied by the application of risk management.